2016
DOI: 10.1039/c6nr02177h
|View full text |Cite
|
Sign up to set email alerts
|

Photo-induced morphological winding and unwinding motion of nanoscrolls composed of niobate nanosheets with a polyfluoroalkyl azobenzene derivative

Abstract: Photo-responsive nanoscrolls can be successfully fabricated by mixing a polyfluoroalkyl azobenzene derivative and a niobate nanosheet, which is exfoliated from potassium hexaniobate. In this study, we have found that the photo-responsive nanoscroll shows a morphological motion of winding and unwinding, which is basically due to the nanosheet sliding within the nanoscroll, by efficient photo-isomerization reactions of the intercalated azobenzene in addition to the interlayer distance change of the nanoscrolls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…18,26,27 In these contexts, we have fabricated the layered nanosheet hybrids composed of polyfluoroalkyl azobenzene derivative (C3F-Azo-C6H: Figure 1a), which is originally synthesized in our group, and inorganic nanosheets to bring out potential photo-functions of molecular assembly in a nanosheet microenvironment. 8,11,12,19 For example, in the clay nanosheet microenvironment, C3F-Azo-C6Hs exceeding over the cation exchange capacity have been intercalated into the interlayer spaces of layered clay nanosheets, 11,19 where C3F-Azo-C6Hs were closely packed between the clay nanosheets due to both the strong hydrophobicity and lipophobicity of the perfluorocarbon chain. Furthermore, it has been found that the photoreactivity for cis−trans photo-isomerization has been remarkably enhanced in the clay hybrid, where the quantum yield exceeded unity (Φ cis−trans = 1.9).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…18,26,27 In these contexts, we have fabricated the layered nanosheet hybrids composed of polyfluoroalkyl azobenzene derivative (C3F-Azo-C6H: Figure 1a), which is originally synthesized in our group, and inorganic nanosheets to bring out potential photo-functions of molecular assembly in a nanosheet microenvironment. 8,11,12,19 For example, in the clay nanosheet microenvironment, C3F-Azo-C6Hs exceeding over the cation exchange capacity have been intercalated into the interlayer spaces of layered clay nanosheets, 11,19 where C3F-Azo-C6Hs were closely packed between the clay nanosheets due to both the strong hydrophobicity and lipophobicity of the perfluorocarbon chain. Furthermore, it has been found that the photoreactivity for cis−trans photo-isomerization has been remarkably enhanced in the clay hybrid, where the quantum yield exceeded unity (Φ cis−trans = 1.9).…”
Section: Introductionmentioning
confidence: 99%
“…12,27,30 Interestingly, the double-walled nanoscroll can undergo a winding and unwinding motion, which is basically due to the nanosheet sliding within the nanoscroll induced by efficient photo-isomerization reactions of the C3F-Azo-C6H. 12 The maximum nanosheet sliding within some nanoscrolls is estimated to be about 280 nm.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations